Equilibrium distributions of discrete non-autonomous graphs - M. Silva, Teresa (2015)
We introduce the notions of equilibrium distribution and time of convergence in discrete non-autonomous graphs. Under some conditions we give an estimate to the convergence time to the equilibrium distribution using the second largest eigenvalue of some matrices associated with the system.